2020
DOI: 10.15243/jdmlm.2020.081.2503
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of arbuscular mycorrhizal fungi spore associated with different land-use types in tropical gold mine

Abstract: Understanding the composition and diversity of arbuscular mycorrhizal fungi (AMF) is imperative for potentially enhancing their ecological role in different terrestrial ecosystems. Land use can have substantial effects on AMF species composition and diversity, but such effects have been explored less in tropical landscapes. In this study, we assessed the effects of disturbances on AMF species richness, observed the potential development of AMF types to produce mycorrhizal biofertilizer bioinoculants. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…The AMF spore abundance recorded in this study were comparable with the findings from different tropical areas [32,39,41,44,85]. Spore densities in this study were higher than the findings conducted by [36,89,90]and lower than those obtained by [91] in Ivory Coast. The differences might be the identification techniques and soil disturbance [8].…”
Section: Amf Spore Abundance Richness and Diversitysupporting
confidence: 86%
“…The AMF spore abundance recorded in this study were comparable with the findings from different tropical areas [32,39,41,44,85]. Spore densities in this study were higher than the findings conducted by [36,89,90]and lower than those obtained by [91] in Ivory Coast. The differences might be the identification techniques and soil disturbance [8].…”
Section: Amf Spore Abundance Richness and Diversitysupporting
confidence: 86%
“…Results of this study showed that the dominant AMF family was Glomeraceae at a percentage of 70%. Several studies also showed the same results, in which Glomeraceae was dominant in the post-mining area of nickel (Prayudyaningsih et al, 2019), coal (Ezeokoli et al, 2020), asphalt (Tuheteru et al, 2022), gold (Tuheteru et al, 2020), and limestone (Suting and Devi, 2021). Glomeracecae was reported to be dominant in the rhizosphere of several tropical tree species .…”
Section: Total Amf Types In Field and Trap Culturementioning
confidence: 56%
“…1, and S. sinousa were discovered in savannah and postmining soil. A. scrobiculata was discovered in post-gold mining owned by PT Panca Logam Makmur and a mining community in Bombana (Tuheteru et al, 2020). AMF discovered in three locations was Glomus sp.…”
Section: Total Amf Types In Field and Trap Culturementioning
confidence: 99%
See 2 more Smart Citations